The Association Between Low Grade Systemic Inflammation and Skin Diseases: A Cross-sectional Survey in the Northern Finland Birth Cohort 1966 - Sinikumpu, S; Huilaja, L; Auvinen, J; Jokelainen, J; Puukka, K; Ruokonen, A; Timonen, M; Tasanen, K (Acta dermato-venereologica, 2018)
Low grade inflammation is associated with many noncommunicable diseases. The association between skin diseases in general and systemic inflammation has not previously been studied at the population level. A whole-body investigation on 1,930 adults belonging to Northern Finland Birth Cohort 1966 was performed and high sensitive C-reactive protein (CRP) level was measured as a marker of low grade inflammation in order to determine the association between low grade inflammation and skin diseases in an unselected adult population. After adjustment for confounding factors the following skin disorders were associated with low grade inflammation in multinomial logistic regression analysis: atopic eczema (OR 2.2, 95% CI 1.2-3.9), onychomycosis (OR 2.0, 1.2-3.2) and rosacea (OR 1.7, 1.1-2.5). After additionally adjusting for body mass index and systemic diseases, the risks for atopic eczema (OR 2.4, 1.3-4.6) and onychomycosis (OR 1.9, 1.1-3.1) remained statistically significant. In conclusion, low grade inflammation is present in several skin diseases.